An Analysis of Students’ Speaking Skill in Giving Suggestion Through Picture Series in Eleventh Grade Students of SMK Negeri 5 Padang - Elda Martha Suri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is motivated by the low ability of students to speak English. The purpose of this study was to determine the ability of students to speak English through Picture Series. The method used in this research was descriptive analysis method. In this research, the population was the second-grade students' of SMKN 5 Padang, the number of the population members was 70 students. The sample of this research was class 2 Design of Building Information and Modeling 2, and the size of the sample was 18 students. In this research, researcher use cluster random sampling. Instrumentation that used in this research was text giving suggestion through picture series. This data was obtained from the results of test given to students, the authors found the value of five criteria of speaking skills in giving suggestion through picture series, vocabulary, grammar, pronunciation, fluency, and comprehension. It can be concluded that the ability of students is moderate, obtained from a score 1 and a score 2 that there are 13 people from 18 students who got moderate (72,2%), and 3 people from 18 students got high scores (16,6%). Based on the research analysis, the researcher was suggested that English teacher give students’ more practice and pay attention especially in speaking. And pay attention for aspect to be used in speaking test, so students understand about the material especially in giving suggestion.Arikunto, S. (2002). Dasar-Dasar Penelitian. Jakarta: Bumi Aksara Brown. (2001). Principles of Language Learning and Teaching. New York: Addison Wesley Longman, Inc.Brown. (2004). Principles of Language Learning and Teaching. San Fransisco: LongmanBrown. (2007). Language Assessment. Principles and Classroom Practices. San Fransisco: LongmanDavies, P. and Pearse. (2000). Success in Language Teaching. Shanghai: Foreign Language Education Press. Gay, L. R. (2009). Education Research: Compentencies for Analysis and Aplication. New York: LongmanGrififths. (2008). Lesson from Language Learners. New York: Cambrige University Press.Harmer, J. (2007). The Practice of English Language Teaching. New york: Longman Group.Hasbullah, et al. (2018). Communication Pattern of Wilayatul Hisbah, Lhokseumawe City in Implementing Amar Makruf Nahi Mungkar. Budapest International Research and Critics Institute-Journal (BIRCI-Journal).P. 194-205.Nunan, D. (2003). Practical English Language Teaching. New York: Mc Graw Hill.Nungroho, Agung. (2008). Improving the Eight Level Students' Speaking Ability Through Picture Series. E-Journal.Pradana, D. et al. (2020). Nasionalism: Character Education Orientation in Learning Development. Budapest International Research and Critics Institute-Journal (BIRCI-Journal).P. 4026-4034Richards, J. C. (2002). Communicative Language Teaching Today. New York: Cambridge University Press.Sadiman, Arief, et,al. (2006). Media Pendidikan: Pengertian, Pengembangan, dan Pemanfaatannya. Jakarta. Rajawali Press.Sudjana. (2003), Media Pendidikan. Jakarta: PT. Raja GrafindoWright, A. (1989). Picture for Language Learning. New York: Cambridge University Press.Wulandari. (2012). The Use of Picture to Improve the Students' Speaking Ability. E-Journal.